Innovation of assessment instruments based on a pragmatics approach on the Mufradat tests - Muhamad Fadhil Husein; R Umi Baroroh; Rianda Ayu Ritnaning Tias; Ade Satria Fauzi Nasution (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study addresses the limitations of conventional vocabulary teaching methods at Pondok Modern Al-Furqon, which focus on rote memorization without assessing students' ability to use vocabulary communicatively. This research aims to develop a pragmatics-based assessment instrument to enhance students' competence in applying vocabulary in real-life contexts. The research adopts a Research and Development (R&D) approach using the ADDIE model. The findings indicate that the developed instrument, consisting of written tests (multiple-choice, short answers, matching pictures) and oral tests (simulations and dialogues) is valid and reliable both technically and pedagogically. Small-scale implementation revealed significant improvements in students' ability to apply vocabulary pragmatically, although some challenges, such as the extended time required for oral tests, were identified. The study concludes that the pragmatics-based instrument effectively supports more applicable Arabic language learning. The implications highlight the importance of integrating pragmatic approaches in vocabulary teaching to improve students' communicative skills in used language